The Perceptions of Students on the Importance of English Speaking Skill in the Tourism Sector - Syahwil Saputra; Endang Komariah; Yuliana Natsir (Universitas Syiah Kuala, 2017)
The objective of this study is to find out the perceptions of students on the importance of English speaking skill in the tourism sector. The instruments used to collect the data were the questionnaire and interview. Both the instruments were adapted from Arslan and Akbarov (2012). The set of interview questions were adjusted by the writer to figure out the perceptions of students toward the importance of English speaking skill in tourism sector. The subjects of this study were the fourth and sixth semester students of Tourism Academy of Muhammadiyah Aceh. The writer took 25 students as the sample. The data were analyzed by using qualitative data analysis (data reduction, data display, and conclusion). Based on the data obtained from both instruments, the findings showed that the majority of students perceived that English speaking skills in the tourism sector was important. It can be seen from the data result based on each category of the questionnaire item. More than 50% of the respondents perceived that English for tourism was attractive to learn. Furthermore, 90% of the respondents stated that English for tourism was useful in finding future jobs. Based on the third category, there were 91% of the respondents stated that English was important in facilitating communication process in the tourism sector. Moreover, there were 56% of the respondents stated there was an impact of speaking English to native language. The last category, 91% of the students perceived that they were aware of basic terms of tourism in English.